The Pollen Morphology of Dragon’s Blood Rattans (Daemonorops spp.) from Sumatra. - Revis Asra; Upik Yelianti; Joko Ridho Witono (PTTI, 2019)
Revis Asra, UpikYelianti & Joko Ridho Witono. 2019. The Pollen Morphology of Dragon’s Blood Rattans(Daemonorops spp.) from Sumatra. Floribunda 6(2): 35–40. — Dragon’s blood rattans (Daemonorops spp.) or locally known as jernang, is one of the well anticipated and economically valuable non timber forest products from Sumatra. The species group produces a red resin on the fruit scale and is one of the main resources of some medicines and colouring. The characteristic of pollen morphology was one of important role in determining the pollination system of dioecious species such as dragon’s blood rattans. The purpose of this study was to examine the pollen characteristic and its relation to the pollination system of four species of dragon’s blood rattans from Sumatra, i.e. Daemonorops aff. propinqua Becc., D. propinqua Becc., D. draconcella Becc. and D. didymophylla Becc. Pollen of dragon’s blood rattans were collected from the secondary forest of Jambi and Bukit Duabelas National Park, then stored in FAA solution, followed by observation using SEM (Scanning Electron Microscope). The pollen of Daemonorops aff. propinqua and D. propinqua have aperture and irregular ex-ornamentation type, while D. draconcella is monocolpus and D. didymophylla is tricolpus. The pollen of Daemonorops aff. propinqua and D. propinqua show uneven exines while the others Daemonorops have even exines. Characters of smooth pollen grainsin D. draconcella and D. didymophylla are indicated that those species associated with wind pollination, whereas sculptured pollen grains in Daemonorops aff. propinqua and D. propinqua are associated with insect pollination.